Malaysian English Language Teachers’ Willingness, Readiness, Needs and Wants to Develop Graphic Oral History ELT Materials - Ibrahim, Said Ahmed Mustafa; Aziz, Azlina Abdul; Said, Nur Ehsan Mohd; Ismail, Hanita Hanim (International Journal of Learning, Teaching and Educational Research, 2023)
Non-native English language teachers have long been de-professionalized being adopters of preponderant globalized English language teaching (ELT) coursebooks that offer an insignificant contribution to their students’ English language learning. This has spurred the design of the “Innovations in Materials Development” (IMD) module to train Malaysian English language teachers in developing graphic oral history ELT materials. This study reports on the initial (needs analysis) phase of the instructional design of the module; not only did the researchers examine the teachers’ willingness and readiness to develop their ELT materials, but they also investigated the teachers’ needs and wants to inform the design of the module. Qualitative findings from in-depth semi-structured individual interviews with five Malaysian in-service English language teachers showed that the teachers are willing to adopt the materials developer role; however, they are not ready as they lack ELT materials development experiences and training. In the context of the prospective module, they need training comprising ELT materials development principles and oral history and graphic novels as pedagogical tools. Moreover, the teachers expressed that they want the training to be practical and to involve group work, guidance, and materials samples. These findings established the need for the IMD module and helped the researchers identify and formulate the specific needs and wants of the teachers for the training to be efficient. https://doi.org/10.26803/ijlter.22.5.5